ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SMP PADA MATERI GERAK LURUS - Weni Afriani; Judyanto Sirait; Erwina Oktavianty (Institut Pendidikan Tapanuli Selatan, 2022)
The learning process of the 2013 curriculum focuses on students who will find out and process individually the information from the learning provided. This causes students to have higher thinking skills. The purpose of this study was to investigate the higher-order thinking skills of class VIII students on the material of straight motion at SMP Pontianak. The study was conducted with a survey involving 150 students from five schools. The research instrument used was a Higher Order Thinking Skill (HOTS) test consisting of 15 questions in the form of reasoned multiple choice. The questions used have three main cognitive dimensions, namely analyzing (C4), evaluating (C5), and creating (C6). The average value of the results of the analysis shows that the students' higher order thinking ability is 56.26 which is included in the sufficient category. As for the three cognitive dimensions of higher order thinking skills, students have a percentage of 54.50% for the level of analyzing (C4) where most of the students cannot read tables and transfer calculation data into tables or graphs, for the level of evaluating (C5) of 48, The lowest 95% is because students have not been right in providing the right solution to the given problem, and the level of creating (C6) is 58.40% where students can arrange experimental designs based on the material in straight motion.